A low-carbohydrate ketogenic diet reduces body mass without compromising performance in powerlifting and Olympic weightlifting athletes - Greene, D. A.; Varley, B. J.; Hartwig, T. B.; Chapman, P.; Rigney, M. (The Journal of Strength and Conditioning Research, 2018)
Weight class athletes use weight-making strategies to compete in specific weight categories with an optimum power-to-weight ratio. There is evidence that low carbohydrate diets might offer specific advantages for weight reduction without the negative impact on strength and power previously hypothesized to accompany carbohydrate restriction. Therefore, the purpose of this study was to determine whether a low-carbohydrate ketogenic diet (LCKD) could be used as a weight reduction strategy for athletes competing in the weight class sports of powerlifting and Olympic weightlifting. Fourteen intermediate to elite competitive lifting athletes (age 34 ± 10.5, n = 5 female) consumed an ad libitum usual diet (UD) (>250 g daily intake of carbohydrates) and an ad libitum LCKD (=50 g or =10% daily intake of carbohydrates) in random order, each for 3 months in a crossover design. Lifting performance, body composition, resting metabolic rate, blood glucose, and blood electrolytes were measured at baseline, 3 months, and 6 months. The LCKD phase resulted in significantly lower body mass (-3.26 kg, p = 0.038) and lean mass (-2.26 kg, p = 0.016) compared with the UD phase. Lean mass losses were not reflected in lifting performances that were not different between dietary phases. No other differences in primary or secondary outcome measures were found between dietary phases. Weight class athletes consuming an ad libitum LCKD decreased body mass and achieved lifting performances that were comparable with their UD. Coaches and athletes should consider using an LCKD to achieve targeted weight reduction goals for weight class sports.